SISTEM INFORMASI RANTAI PASOK PENETASAN D.O.C AYAM BOILER: (STUDI KASUS: GIRIWANGI JAYA FARM) - Siti Yuliyanti; Aep Saepudin; Rahmat Zaenal (JURTIK:Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2019)
Such technology has a rapid impact on the whole life, especially the provision of information for an organization / agency or company that requires a data management system that is fast, precise and accurate. To support the effectiveness of this thesis entitled, "“Sistem Informasi Rantai Pasok Penetasan D.O.C AYAM BOIER di Giriwangi Jaya Farm”. The background of the problem at the current Giriwangi Jaya Farm is From development, productivity and efficiency in an organization / agency or company in solving management problems, especially providing information regarding hatching data to the head of the hatchery data processing system aims to create effective and efficient performance, because it is easier to obtain information and does not need to waste much time Keywords: Information system, hatching, boiler chicken